Diaporthe species associated with the maritime grass Festuca rubra subsp. pruinosa - Toghueo, Rufin Marie Kouipou; Vázquez de Aldana, Beatriz R.; Zabalgogeazcoa, Iñigo (Frontiers in Microbiology, 2023)
Festuca rubra subsp. pruinosa is a halophytic perennial grass growing in sea cliffs where plants are highly exposed to salinity and marine winds, and often grow in rock fissures where soil is absent. Diaporthe species are one of the most abundant components of the root microbiome of this grass and several Diaporthe isolates have been found to produce beneficial effects in their host and other plant species of agronomic importance. In this study, 22 strains of Diaporthe isolated as endophytes from roots of Festuca rubra subsp. pruinosa were characterized by molecular, morphological, and biochemical analyses. Sequences of the nuclear ribosomal internal transcribed spacers (ITS), translation elongation factor 1-α (TEF1), beta-tubulin (TUB), histone-3 (HIS), and calmodulin (CAL) genes were analysed to identify the isolates. A multi-locus phylogenetic analysis of the combined five gene regions led to the identification of two new species named Diaporthe atlantica and Diaporthe iberica. Diaporthe atlantica is the most abundant taxon in its host plant, and Diaporthe iberica was also isolated from Celtica gigantea, another grass species growing in semiarid inland habitats. An in vitro biochemical characterization showed that all cultures of D. atlantica produced indole-3-acetic acid and ammonium, and the strains of D. iberica produced indole 3-acetic acid, ammonium, siderophores, and cellulase. Diaporthe atlantica, closely related to the pathogen of cucurbits D. sclerotioides, caused a growth reduction but no plant lesions when inoculated in cucumber, melon, and watermelon.